PENINGKATAN HASIL SAYURAN LOKAL KABUPATEN LUMAJANG DI LAHAN TERBATAS - Furoidah, Nanik; Sri Wahyuni, Endang (JURNAL AGRI-TEK, 2016)
The purpose long-term research is to provide information to the public about nutrition concentration ready-made efficient for optimal growth on different varieties of lettuce in particular and as a solution to the community Lumajang in utilizing the space around their home for growing hydroponically, in particular vegetable plants as efforts to improve the lives and well-being through nutrition families. The study began with the seeding of lettuce on rockwool, and then seedlings have emerged at least three leaves grown in netpot and placed on the shelf hydroponics with fertigation techniques, where the results can be harvested 45 days after planting (DAP). Lettuce vegetable farming with hydroponics technique is a kind of research and development in terms of cultivation techniques. Analysis of the data in this study using a completely randomized design (CRD) with factorial pattern 3x3 consisting of the first factor, namely the treatment nutrient concentrations AB mix of 350 ppm, 450 ppm and 550 ppm, and the second factor is the treatment sorts of varieties of lettuce consists of varieties of Butterhead, Grand Rapid and General. The growth parameters were observed: plant height, leaf number, root length, fresh weight and dry weight of plants. The results showed that the treatment concentration of 550 ppm provides the best growth response in plants lettuce, especially General varieties and followed Grand Rapid and Butterhead varietiesKeywords: hydroponics, nutrient AB mix concentrations, lettuce varieties